Towards new animal models of pure hypoxic Lance-Adams syndrome: Negative results - Geoffroy Vellieux; Delphine Roussel; Anthony Pinto; Nathalie Mougenot; Vincent Navarro (PLoS ONE, 2026)
Lance-Adams syndrome is a severe and disabling posthypoxic myoclonus in humans. Its underlying mechanisms are still unknown. We aimed to develop a new animal model of Lance-Adams syndrome. We performed our procedures on Sprague-Dawley rats monitored for basic cardiorespiratory parameters. The Group 1 was sedated and submitted to hypoxia in a dedicated cage where oxygen was replaced with nitrogen. The Groups 2 and 3 were sedated, intubated, ventilated, and submitted to anoxia with the replacement of oxygen by nitrogen in the ventilatory circuit, either continuously (Group 2) or intermittently (Group 3). Rats benefited from cardiopulmonary resuscitation. Each rat was evaluated daily for spontaneous, wandering-induced, and auditory stimuli-induced myoclonic jerks, for the latter using a quantitative myoclonus score. In the Group 1 (n = 19), the duration of hypoxia was 25 ± 20 min for the surviving animals (n = 14/19) and minimal partial pressure of oxygen in the cage was 7.2 ± 0.8%. In the Group 2 (n = 38), the duration of anoxia was 5.6 ± 1.9 min for the surviving animals (n = 23/38). In the Group 3 (n = 30), the total duration of anoxia was 15 ± 3.5 min in the surviving animals (n = 15/30). These three procedures did not allow for generating a myoclonic phenotype. Some refinements of hypoxic/anoxic procedures are still needed to develop an animal model of posthypoxic myoclonus that would be a precious tool to understand better the pathophysiology of Lance-Adams syndrome.